2008
DOI: 10.2500/aap.2008.29.3098
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide levels during treatment in patients hospitalized with asthma

Abstract: The time required for fractional excretion of nitric oxide (FE(NO)) measurements to acutely change after systemic corticosteroids is unknown, limiting the usefulness of this biomarker in hospital treatment and discharge decisions. The purpose of this study was to follow FE(NO) measurements of hospitalized adult patients with asthma receiving therapy and to correlate FE(NO) with forced expiratory volume in 1 second percent predicted (FEV(1)%). Ten acute asthmatic patients who required hospitalization were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…15 There is also a paucity of data reporting measurements of FENO and lung function in children during hospitalization for acute asthma. 1618 Our finding of no correlation between enrollment lung function and enrollment FENO is consistent with data reported by Baptist et al 16 The mean FENO concentrations in their patients before discharge from the hospital were slightly higher than those in our patients (38.4 vs. 31.5ppb), and the average enrollment FEV1 in their patients was also lower (64.4% vs. 76.9% predicted). These differences could be explained by their cohort having either more severe asthma or being more acutely ill at the time of enrollment lung function measurements.…”
Section: Discussionsupporting
confidence: 91%
“…15 There is also a paucity of data reporting measurements of FENO and lung function in children during hospitalization for acute asthma. 1618 Our finding of no correlation between enrollment lung function and enrollment FENO is consistent with data reported by Baptist et al 16 The mean FENO concentrations in their patients before discharge from the hospital were slightly higher than those in our patients (38.4 vs. 31.5ppb), and the average enrollment FEV1 in their patients was also lower (64.4% vs. 76.9% predicted). These differences could be explained by their cohort having either more severe asthma or being more acutely ill at the time of enrollment lung function measurements.…”
Section: Discussionsupporting
confidence: 91%
“…While potentially appealing, given the cost and availability of these tests, further research is needed to evaluate the clinical benefit of incorporating biomarkers of eosinophilic airway inflammation in the acute care setting 58,59…”
Section: Discussionmentioning
confidence: 99%
“…Should the asthma worsen, such a relatively large ACQ score increase could potentially be classified as a moderate exacerbation according to ATS/ERS recommendations [24]. Previous studies have already reported a paradoxical parallel increase in FEV1 and FENO during the recovery phase of an acute severe exacerbation [25,26]. Opposite FENO-FEV1 moves were not reported in those studies that involved relatively small numbers of patients, who experienced severe rather than moderate exacerbation.…”
Section: Discussionmentioning
confidence: 75%